Numerical study of the thermal performance of solar chimneys for ventilation in buildings - Charitar, Deepti (Energy Research Centre, 2016)
Building ventilation is crucial for improving the indoor air quality and thermal comfort. Nowadays, mechanical ventilation systems such as air conditioning and fans are most commonly used in buildings. However, these devices consume a lot of electricity which is mainly generated from the combustion of fossil fuels, resulting in the release of greenhouse gases and thereby contributing to climate change. Consequently, it is essential to switch to natural ventilation systems which are environmentally friendly as they are based on renewable sources of energy. One such type of natural ventilation system is the solar chimney which can either be roof-mounted or wall-mounted in buildings. The aim of this study was to develop a mathematical model for assessing the thermal performance of roof-mounted (inclined) and wall-mounted (vertical) solar chimneys. The model was validated using numerical simulations in MATLAB. Different configurations of solar chimneys were designed and modelled in MATLAB in order to compare their performances, in terms of the ventilation rate expressed as the number of air changes per hour, ACH. Raw climatic data, including the intensities of global and diffuse solar radiation on a horizontal plane, wind speed and ambient temperature were obtained for Stellenbosch, located in the Western Cape Province of South Africa. This was used for the MATLAB modelling of the solar chimneys. The effects of inclination angle, air gap, chimney height and view factor on the thermal performance of solar chimneys were explored in this study.